Avaliação de argilas naturais e organofílicas nas propriedades reológicas de emulsões base óleo para aplicação em fluidos de perfuração - Ramalho, Wênnya Joyce Carneiro Rodrigues (2021)
Due to their high adsorption power, bentonite clays have been increasingly the subject of scientific studies. As a result, bentonites are widely applied in the most varied areas, ranging from the metallurgical industry to the oil industry. In the oil sector, they are used to act as viscosifying agents, aiming to ensure greater efficiency in the transportation of debris to the surface. The properties of drilling fluids are extremely important for the achievement of successful oil well drilling. This research aims to evaluate the influence of the type and concentration of natural and organophilic bentonite clays on the viscoelastic parameters of emulsified fluids for application in vegetable oil based drilling fluids. Initially, the raw slime-green clay was submitted to the beneficiation process, aiming to purify it, then, a part of this clay was submitted to the organophilization process, and finally, these clays were used in the preparation of the emulsions. The clay samples were characterized by CTC, DRX, FRX, AG AND TG / DTA. After preparing the emulsions, they were first subjected to rheological tests to obtain the flow curves, then this same sample was subjected to oscillatory scanning tests in order to obtain the viscoelastic parameters: storage module (G ') and energy loss or dissipation module (G ”). From the results, it was possible to verify the efficiency of the purification of the raw slime-green clay. The flow curves showed better adjustments of the mass proportions: 50/50, 70/30 and 80/20 (O / W) to the Newtonian model, and the proportions 90/10 and 95/05 (O / W) to the Herschell- Buckley. All emulsions were characterized as low flow resistance and dilating emulsions (n> 1). Only two proportions of the organophilic slime-green clays and cloisite 20A were physically stable, being evidenced by obtaining G ”> G 'and being totally independent of the angular frequency (ω), being possible to be applied as drilling fluids.